ANALYSIS OF DEFENSE COOPERATION AGREEMENT BETWEEN INDONESIA AND SINGAPORE IN 2007–2017 THROUGH DEFENSE DIPLOMACY GOAL VARIABLE - Milia, Jana; Kurniawan, Yandry; Poespitohadi, Wibisono (Jurnal Pertahanan: Media Informasi tentang Kajian dan Strategi Pertahanan yang Mengedepankan Identity, Nasionalism dan Integrity, 2018)
Defense cooperation agreement between Indonesia and Singapore has been signed on April 27th 2007 in Tampak Siring, Bali by both country’s defense Minister, signifying a further comprehensive agreement based on the content of the DCA (Defense Cooperation Agreement). This defense agreement, in addition of being a continuation of other previous defense cooperation such as Military Training Area in 1995 until 2003, is also a further initiative of Singapore in order to build a mutually beneficial cooperation. In fact, this agreement has also been packaged with extradition agreement which was the initiative of Indonesia. Although the agreement has been signed and agreed by both countries, this agreement was not ratified by Indonesian House of Representatives. Thus, this research will explain about factors or variables that causes the failure of Singapore defense diplomacy. This research uses liberalism perspective, defense diplomacy and bilateral diplomacy concept. The employed research method is analytical descriptive method. Data is collected through interview with 7 informants including academicians, practioners, and other related expert. The data is also obtained from various literatures. Based on 4 defense diplomacy goals variables such as Diplomacy, National Interest, Defense Instrument Usage, Peacetime and Potential Enemy, this research finds that Defense Cooperation Agreement in 2007-2017 has not been succsesful yet because there was a difference between Indonesia’s and Singapore’s national interest. The difference came from the division in Indonesia between its government and parliament where the Government prioritized beneficial cooperation while the Parliament prioritized sovereignty principle.